THE HIDDEN SIDE OF DOMESTIC VIOLENCE: ABUSED MEN IN INTIMATE HETEROSEXUAL RELATIONSHIPS - Mqakelana, Noluthando (New Voices in Psychology, 2016)
Domestic violence is one of the major social issues that characterize our country, both as a contributing factor to other social problems and as a result of other social problems. Domestic violence has been made to be only an issue that affects women; it has been gendered. Men are only brought into domestic violence discourse and research only as perpetrators. However, it affects both women and men as men can also be victims of domestic violence. Domestic violence rates have increased regardless of developments in legislation. In addition, role players in the implementation of legislation tend to emphasize more on female victims which leaves male victims marginalized. This leads to male victims suffering in silence and thinking that there are no interventions for them. This paper explored experiences of abused men in intimate heterosexual relationships using qualitative approach. Data collection took a form of in-depth individual interviews. Data was analyzed using thematic content analysis. Findings indicate that men are also victims of domestic violence and are willing to share their experiences; however there are limited platforms for male victims. Their reasons for staying are multifaceted such as giving their children an opportunity to grow up with both parents. Effects of domestic violence ranged from psycho-emotional to professional development. Social workers as professionals need to sensitize themselves to the reality of male victims of domestic violence and acknowledge that men can also be victims.